An overview of climate finance in India - Bhaskar, Dr.Reddy; Srivastava, Bhawna (Nimitmai Review Journal, 2021)
At presentthe world is facing dual challenges of Covid-19 and climate change. India has been hailed as a global leader by many global leaders for its efforts to tackle the climate change and Covid-19. Climate change has several consequences on development, food and water security, health, and gender equity and poverty alleviation efforts of India. The climate financing efforts in developing countries has become an important global issue for climate governance. Climate finance is a keystone of global assistance to deal with climate change related risks. It is based in narrative that climate change is deadly, expensive, and that those least responsible for causing it are being hardest hit. Accelerating the climate finance to deal with climate change related risk still remains a key challenge in many developing countries including India. The UN Framework Convention on Climate Change (UNFCCC) involves a group of rich and developed countries to support financial assistance to developing nations to deal with climate change. This was based on the Common but Differentiated Responsibilities (CBDR) principle, which was formalized in the Earth Summit in Rio de Janeiro, 1992. India is the world’s fourth-largest emitter of greenhouse gases but imparts insignificant harm. The fifth Assessment Report (AR5) of IPCC (2014) confirmed India’s high vulnerability and exposure to climate change. It has also advocated that climate change will slow India’s economic growth, impact health and development, make poverty reduction more difficult and diminish the food security. In Intended Nationally Determined Contribution (INDC), India has set a figure of USD 2.5 trillion (at 2014-15 prices) as its price for attaining its mitigation and adaptation targets by 2030. Apart from the making budgetary allocations, the government sustains climate action through the cuts in subsidies, increase in taxes on petroleum and diesel, market mechanisms such as Perform Achieve and Trade (PAT) and Renewable Energy Certificates (RECs) and regulatory regimes such as Renewable Purchase Obligations (RPOs). However, with high inflation and slowing growth, the country faces various major challenges like poverty, health, education, sanitization, corruption and gender differences which hinder the climate change goal. In the present review, we evaluated some of the most recent and existing mechanisms, activities and challenges of climate finance related climate finance in India.